Educating for civic dialogue in an age of uncivil discourse - Gunn, Dennis, 1966- (New york Routledge, 2020)
"Educating for Civic Dialogue in an Age of Uncivil Discourse addresses an urgent challenge-to help students learn the skills of civic engagement-by offering a framework for authentic cosmopolitan education. As an invitation to ongoing civil dialogue with diverse voices in the classroom, the book aims to foster the skills of democratic and global citizenship that allow students to find their voice as local, national, and global citizens outside of the classroom. It suggests practical ways that teachers can promote the skills of attentive listening, intelligent questioning, reasonable positioning, and responsible dialogue in order to encourage authentic civic discourse. It also outlines specific pedagogical strategies designed to foster students' cosmopolitan competencies as democratic and global citizens"--
Introduction: overcoming Babel -- Broken conversations : educating globalized citizens in a polarized world -- Globalized conversations : teaching for cosmopolis -- Engaging conversations : developing the skills of civic discourse -- Critical conversations : teaching critical thinking for democratic and global citizenship -- Creative conversations : re-imagining cosmopolitan classrooms for the 21st century.
Includes bibliographical references and index.
Keywords: Cosmopolitanism -- Study and teaching; World citizenship -- Study and teaching; Civil society -- Study and teaching; Discussion -- Study and teaching